Digital Marketing Effectiveness Through Social Media (Facebook, TikTok, Instagram) Against Te Boo Boo - Setiawan, Gabriellla Alicia; Nugroho, Agus Cahyo; Harnadi, Bernardinus (Journal of Business and Technology, 2023)
Offline and online digital marketing strategies for brand recognition have different effects on product sales, so researchers conduct research using brand recognition strategies through social media, Instagram, Facebook, and TikTok. This research aims to measure the effectiveness of digital marketing through social media on Te Boo Boo brand awareness. Measuring the engagement rate of posts on social media can be used to determine how much people know about the Te Boo Boo business. The method used in this research is to measure the engagement rate of daily posts on social media Instagram, TikTok, and Facebook per month. Daily engagement rate measurement data were collected for two months. Comparisons were made in the context of days between engagement rates and daily sales data for two months. The results found in the study were that the comparison between engagement rate and sales results showed a correlation. However, it was insignificant due to the influence of offline events that were also applied, such as participating in bazaars and night markets. Research showed that when promotions used endorsement programs, sales showed a sharp upward pattern.